Myths and [mis] perceptions changing U.S. elite visions of Mexico - Brody, Julián (El Colegio de México, 1998)
This book goes beyond my original intentions. As I became increasingly aware of the evolution or U.S. perceptions and the impact of the ideas on reality, I was also able to reinterpret certain aspects of Mexico's recent history. In this process, I confirmed, adjusted, or put to rest a numbers of myths about Mexico, Mexicans and the role of the culty of uprooting well established beliefs--The author